Factors Associated with Korean Medicine Utilization during the COVID-19 Pandemic Period (2019–2023): A Panel Analysis of the Korea Health Panel - Changyon Han (Journal of Korean Medicine, 2026)
Objectives: This study investigates factors associated with Korean Medicine (KM) outpatient utilization in 2019–2023, a period that includes the COVID-19 pandemic, using the Andersen behavioral model. It analyzes individual-level panel data to distinguish factors associated with entry (whether KM is used) from those associated with intensity (how much is used), across three dimensions.Methods: This study estimated three outcomes using household-member random-effects panel models in accordance with Andersen’s behavioral model: KM outpatient utilization (panel logit), annual visit days (random-effects negative binomial, users only), and annual expenditure (gamma generalized linear model (GLM) with a log link, users only). Unweighted random-effects models were used for the main analysis, and complex-survey design-based estimates using the longitudinal weight were provided as a supplementary check.Results: Predisposing, enabling, and need factors were all significantly associated with KM utilization, although the associated dimensions differed by factor group. Predisposing factors—older age, female sex, and marriage—were associated with entry and visit days, but not with expenditure. Enabling factors were associated with all three dimensions, most prominently with expenditure, which increased with household income quintile, whereas private insurance was associated with entry. Need factors—the presence of chronic disease (rather than comorbidity severity, CCI) and poorer self-rated health—were consistently associated with higher visit days and expenditure, and health-conscious individuals used KM more.Conclusions: Within the two-part framework, KM outpatient use in 2019–2023 showed a dual pattern: entry was associated with socioeconomic factors, and intensity with health need, consistent with KM’s role as a complementary medical service.